Pengaruh Senam Nifas terhadap Penguatan Otot perut Post Partum - Dalila, Sastri, Dwi Rosella K, S.St FT., M.Fis, Totok Budi Santoso , S.Fis , MPH (2015)
Postnatal exercise is a motion exercises that should be undertaken as soon as possible after give birth, so that the muscles are experiencing stretches during pregnancy and childbirth can return to normal conditions. Gymnastics postpartum is done to restore/ enhance the reproductive organs especially the abdominal muscle in its original state. The repair of abdominal muscle strain/ abdomen after giving birth, nurture and strengthen the abdominal muscles, pelvic floor muscles, and muscle movement, launched blood circulation. It is important for the mother after childbirth to do gymnastics parturition, among others: Due to the pelvic stretch of hips muscles, the loose of abdominal wall muscles and the change of body. This research was conducted in Makamhaji under the village health clinic permission of Ngudi Waras Gobayan Kartasura Makamhaji on July 4 april 2015 ". This research done by using a pre-experimental design with One Group Pre and Post Test Design Approach to determine the benefits of postnatal exercise to improve the strength of the abdominal muscles. Samples that meet the criteria of inclusion and exclusion were 13 people. To find out the differences before and after postnatal exercise, Post test I (given one time postnatal exercise), and after post-test II (given three times postnatal exercise), and after the post-test III (given six times postnatal exercise performed by Wilcoxon test. The results of post test I obtained p value = 0.005 <α = 0.05, which means that there are significant differences between pretest measurement results after one time, three times and six times of the provision of post-partum exercise intervention. It means that postnatal exercise has significant effect to restore the impaired abdominal MMT for the mother after give birthand change the value of MMT abdomen. Keywords: postnatal exercise, postpartum, abdominal muscle strength